Catalyzing Research to Optimize Cancer Survivors' Participation in Work and Life Roles. (October 2019) - Newman, Robin M.; Alfano, Catherine M.; Radomski, Mary Vining; Pergolotti, Mackenzi; Wolf, Timothy J.; Sleight, Alix G.; Bryant, Ashley Leak; Voelbel, Gerald T.; de Moor, Janet S.; Nitkin, Ralph; Daniels, Elvan; Braveman, Brent; et al.
Participation refers to a state of health in which a person is able to fully engage in roles and life situations. Adults living with and beyond cancer often report persistent participation restrictions that affect their productivity and quality of life. The American Occupational Therapy Foundation convened a group of scientists from seven different disciplines in a Planning Grant Collective (PGC) to stimulate research to identify scalable ways to preserve and optimize participation among cancer survivors. Participants identified challenges, prioritized solutions, and generated novel research questions that move beyond symptom and impairment mitigation as outcomes to identify interventions that improve participation in roles and life situations. This article summarizes the PGC discussion and recommendations regarding three challenges: (a) the dynamic and multi-faceted nature of participation, (b) a need to integrate the concept of participation within the culture of oncology, and (c) identification of priority areas in which new lines of research regarding participation would be most impactful.